Adverse effects of parenteral dexamethasone in the treatment of pemphigus vulgaris - Uddin, Mohammad Jamal; Islam, A.Z.M Maidul; Ali, Mohammad Eakub; Wahab, Md. Abdul; Khondker, Lubna (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Pemphigus vulgaris is associated with high morbidity as well as significant mortality rate. Today the risk of death in pemphigus from the side effect of oral prednisolone is greater than risk of death from the disease itself. Objective: To observe the adverse effects of parenteral dexamethasone compared with oral prednisolone in the treatment of pemphigus vulgaris. Methods: An interventional study was carried out in the department of Dermatology and Venereology, Bangabandu Sheikh Mujib Medical University, Dhaka, Bangladesh. Total number of patients was thirty and among them fifteen patients were treated with parenteral dexamethasone (Group-A) and other fifteen were treated with oral prednisolone (Group-B). Results: The study showed statistically significant differences of skin lesion as well as mucosal lesion of pemphigus after 6 weeks of therapy between of two groups (P<0.05). The most common adverse effects were increased body weight(40%), increased appetite(40%), and puffy face(40%) in dexamethasone group. In prednisolone group, these side effects were 60% of the subjects. Other side effects in dexamethasone group were hyperglycemia (33.33%), hypertension (26.66%), and sleep disturbance (13.33%). In prednisolone group, other side effects were hyperglycemia(33.33%), hypertension(40%), gastritis (33.33%), nausea, vomiting (13.33%) in each , reactivation of tuberculosis, herpes zoster infection, sleep disturbance, and mood change were 6.66% in each group. Conclusion: In the light of the findings of the study, we conclude that each of the treatment of dexamethasone group and prednisolone group is individually effective and safe in the treatment of pemphigus vulgaris but adverse effects are less in parenteral dexamethasone group than oral prednisolone group. So parenteral dexamethasone can be used as an alternative drug in the treatment of pemphigus vulgaris.